2023
DOI: 10.1038/s12276-023-01076-z
|View full text |Cite
|
Sign up to set email alerts
|

A single-cell atlas of in vitro multiculture systems uncovers the in vivo lineage trajectory and cell state in the human lung

Abstract: We present an in-depth single-cell atlas of in vitro multiculture systems on human primary airway epithelium derived from normal and diseased lungs of 27 individual donors. Our large-scale single-cell profiling identified new cell states and differentiation trajectories of rare airway epithelial cell types in human distal lungs. By integrating single-cell datasets of human lung tissues, we discovered immune-primed subsets enriched in lungs and organoids derived from patients with chronic respiratory disease. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…These findings are in line with the inability of SARS-CoV-1-related Coronavirus WIV1 to propagate in Egyptian fruit bats 77 . By contrast, MERS replicated in distal lung bat organoids and induced a strong type-I/III interferon-mediated antiviral response; which occurs only to a limited extent in differentiated primary human airway epithelial cultures as previously reported 60,80 . Although MERS has not been found in Rousettus aegyptiacus, the related group 2d Betacoronavirus HKU9 RNA has been detected in Rousettus bats in independent sampling studies 99,100 .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…These findings are in line with the inability of SARS-CoV-1-related Coronavirus WIV1 to propagate in Egyptian fruit bats 77 . By contrast, MERS replicated in distal lung bat organoids and induced a strong type-I/III interferon-mediated antiviral response; which occurs only to a limited extent in differentiated primary human airway epithelial cultures as previously reported 60,80 . Although MERS has not been found in Rousettus aegyptiacus, the related group 2d Betacoronavirus HKU9 RNA has been detected in Rousettus bats in independent sampling studies 99,100 .…”
Section: Discussionsupporting
confidence: 78%
“…Differential gene expression analysis further demonstrated specific transcriptional cell states in these rare cell types, including well-known markers and several novel candidate genes that warrant further exploration (Figure 2L). Our data shows that adult airway stem cell derived organoids from the Egyptian fruit bat recapitulate the complex cell type diversity of the stereotypical mammalian upper and lower airways, including the presence of rare specialized cell types important for mucosal immunity that are either absent or infrequently observed in single-cell RNA-sequencing data of human airway organoid cultures 60 . Our novel resource should allow researchers to explore bat airway epithelial cell states at unprecedented detail.…”
Section: Single-cell Rna Profiling Of Egyptian Fruit Bat Airway Organ...mentioning
confidence: 66%
See 1 more Smart Citation
“… Shivaraju et al (2021) showed that after exposure to hypoxia ( Box 1 ), lineage-traced basal cell progenitors in the murine trachea gave rise to PNECs. Based on pseudotime trajectory analysis of single-cell multiomics data of airway organoids derived from human distal lung tissue, it has been proposed that basal cells might undergo differentiation into PNECs also in adult human lungs ( Lee et al, 2023 ). Lineage-tracing experiments in this human organoid model are needed to confirm the basal cell to PNEC trajectory proposed by pseudotime analysis.…”
Section: Pnecs In Adult Tissuementioning
confidence: 99%
“…There have been several studies applying single-cell RNA-sequencing (scRNA-seq) to examine host responses to SARS-CoV-2 17 , 18 , 19 , 20 , 21 using infected cells collected directly from patients 20 , 22 or from 3D organoids/air-liquid-interface (ALI)-cultures. 23 While in vivo samples provide the biological relevance and complexity of host-pathogen interactions, ALI-culture settings allow a tightly controlled environment for assessing viral infections at the epithelial level without the interference of immune cells and allows the control of viral strain applied to the cells. Also, the time of infection/exposure to virus can also be accurately determined, providing an enhanced temporal assessment.…”
Section: Introductionmentioning
confidence: 99%